ANALYSIS INSTAGRAM CONTENT IN THE POLITICAL COMMUNICATION STRATEGIES OF THE 2024 INDONESIA PRESIDENTIAL CANDIDATES - Febrianto, Arrois; Devi Purnamasari (Sociae Polites, 2023)
The current phenomenon of Generation Z and Millennials' distrust of politics in Indonesia is a serious challenge that will be faced in the 2024 elections. The digital era has changed the political landscape drastically, with online media playing a key role in influencing political communication, public participation, campaigns, and general elections. In their campaign efforts, the two main presidential candidates have utilized the Instagram platform in their styles. This reflects the importance of social media as a tool to gain support, especially from the younger generation who tend to be technologically savvy. This research was conducted to examine the comparison of campaign content uploaded on the Instagram accounts @prabowo and @ganjar_pranowo. The theory used in this research is Political Communication Strategy and 4C Theory (Content, Communication, Collaboration, Connection) as a further analysis using the qualitative comparative study approach method. The results of this research clearly illustrate how the two presidential candidates use Instagram as a platform for their rhetorical expression, political actions, and lobbying efforts. In general, the @prabowo account exudes a strong spirit of nationalism through its content, while @ganjar_pranowo differentiates itself with its approach to society on current issues.